A Theory of Socialism and Capitalism - Fiuza, Lucas (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2016)
Resenha do Livro: A Theory of Socialism and Capitalism Autor: Hans-Hermann Hoppe ISBN: 978-1-933550-73-2